2022
DOI: 10.3390/ijms23116083
|View full text |Cite
|
Sign up to set email alerts
|

Newly Emerged Antiviral Strategies for SARS-CoV-2: From Deciphering Viral Protein Structural Function to the Development of Vaccines, Antibodies, and Small Molecules

Abstract: Coronavirus disease 2019 (COVID-19) caused by the infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become the most severe health crisis, causing extraordinary economic disruption worldwide. SARS-CoV-2 is a single-stranded RNA-enveloped virus. The process of viral replication and particle packaging is finished in host cells. Viral proteins, including both structural and nonstructural proteins, play important roles in the viral life cycle, which also provides the targets of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…According to our results, 99.72% of Nsp11 protein worldwide (from 99.61% in Africa to 99.93% in Oceania) did not illustrate any mutation. The independent function of NSP11 has not been characterized yet; however, NSP11 contributes to the interaction between the SARS-CoV-2 and host cell membrane [ 98 ]. Kaushal et al analyzed the rate of mutation accumulation between January 19 to April 15, 2020, in the USA SARS-CoV-2 genome.…”
Section: Resultsmentioning
confidence: 99%
“…According to our results, 99.72% of Nsp11 protein worldwide (from 99.61% in Africa to 99.93% in Oceania) did not illustrate any mutation. The independent function of NSP11 has not been characterized yet; however, NSP11 contributes to the interaction between the SARS-CoV-2 and host cell membrane [ 98 ]. Kaushal et al analyzed the rate of mutation accumulation between January 19 to April 15, 2020, in the USA SARS-CoV-2 genome.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of hot spots of intra-sample genetic diversity suggests that at least some of these mutations are not only de novo mutations generated by the low fidelity RNA-dependent RNA polymerase and might be selected and found in major viral variants. In this view, Zhang et al reported that some of the minority SARS-CoV-2 quasispecies that were detectable during the early stage of the pandemic did forecast later circulating mutants and variants [ 5 , 6 ]. Thus, studies of viral quasispecies as the present one may reveal nucleotide positions in the SARS-CoV-2 genome that particularly exhibit genetic diversity and variability, and hence possible virus evolutionary pathways and critical genomic regions for the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Its genome is 29,903 nucleotide-long (based on the genome of the Wuhan-Hu-1 isolate, GenBank Accession NC_045512.2) and harbors 14 open reading frames (ORFs) that encode 31 structural, non-structural, or regulatory/accessories proteins. These proteins include, in the order of their genes from the 5′ region to the 3′ region of the genome [ 3 , 4 ]: two large polyproteins, ORF1a and ORF1b, that are proteolytically cleaved by a virus-encoded protease into 16 non-structural, enzymatic proteins (NSP1-16) involved in viral replication and that notably comprise the RNA-dependent RNA polymerase, an endonuclease, and a helicase; four structural proteins including the spike (S) protein that binds to the angiotensin-converting enzyme 2 (ACE2) receptor of the host cells, the envelope (E) protein, the membrane (M) protein, and the nucleocapsid (N) protein, all these proteins being common to all coronaviruses and considered as major targets for the development of antiviral drugs and vaccines [ 3 , 5 , 6 ]; and eleven regulatory/accessory proteins, ORF3a, ORF3b, ORF3c, ORF3d, ORF6, ORF7a, ORF7b, ORF8, ORF9b, ORF9c, and ORF10. The SARS-CoV-2 genome is flanked by two untranslated regions (UTR) (5′UTR and 3′UTR).…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviruses, enveloped viruses with a single, positive-strand RNA, are common in animals, including humans [ 1 ]. These viruses are spherical, with a diameter of about 100 nm, and have distinctive crown-like projections or spikes on their surfaces, hence the name “corona” (Latin for crown) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%